Rendre les alternatives visibles. Une critique écosophique du dualisme “durable” - De Fazio, Gianluca (2021)
The aim of the present paper is to introduce a philosophical critique of the concept of sustainability through the ecosophy outlined by F. Guattari. According to the ecosophical perspective, the idea of sustainability hides the transcoding processes of technological innovation. The first part of the paper develops a genealogy of transcoding processes by regarding them as an ecosophical object. The second one analyses the basic dualism of sustainability in detail: ecocentrism vs technocentrism.